Health Promotion Media To Behavior Change On Exclusive Breastfeeding Mothers - Sudarwati Nababan (Universitas Airlangga, 2019)
Background: Exclusive breastfeeding is a process of giving only breast milk to babies since they are born until they are six month old. Membramo Public Health Office reported that according to the health profile report from Kobakma Public Health Centre, the exclusive breastfeeding program has not achieved the national target, which is 80%, only 55,4% babies who got exclusive breastfeeding in 2015. The chairperson from Kobakma Public Health Centre states that one of the problem is the misunderstanding about breastmilk among mothers in the surroundin. They throw their breast milk away and feed their babies with formulated milk during the period of postpartum for three months. Purpose: This study is aimed to know the effect of counseling program using two sided flipchart on exclusive breastfeeding. Methods: This study uses quasi experiment method with non equivalent control group. The samples of this study are mothers who have 0-6 month old babies and live in working area of Kobakma Public Health. 60 mothers are selected using purposive sampling technique. The Instrument of this study uses questionnaire, data ccollection was done by face to face method. The data was then analyzed using chi square and wilcoxon signed rank test. Results: The result of this study shows significant difference in the improvement of knowledge, behaviour, and practice before and after the counseling program of the intervention group (p=0,000). Conclusion: The implementation of counseling program using two sided flipcharts is effective to improve mothers’ knowledge, behaviour and practice in exclusive breastfeeding.